2018
DOI: 10.1007/s10126-018-9853-1
|View full text |Cite
|
Sign up to set email alerts
|

Ruegeria sp. Strains Isolated from the Reef-Building Coral Galaxea fascicularis Inhibit Growth of the Temperature-Dependent Pathogen Vibrio coralliilyticus

Abstract: The coral microbiome has attracted increased attention because of its potential roles in host protection against deadly diseases. However, little is known about the role of coral-associated bacteria against the temperature-dependent opportunistic pathogen Vibrio coralliilyticus. In this study, we tested whether bacteria associated with the reef-building coral Galaxea fascicularis could inhibit the growth of V. coralliilyticus. Twenty-nine cultivable bacteria were successfully isolated from a healthy colony of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 59 publications
1
39
0
Order By: Relevance
“…Recently, the beneficial roles of bacteria in the coral holobiont have been investigated (6). These functions include defense against pathogens (12,13) and the cycling of nutrients such as nitrogen (14) and sulfur (15). Moreover, coral-associated bacteria have been proposed to be involved in coral resistance to bleaching (16,17), which has a devastating impact on reefs worldwide (4).…”
mentioning
confidence: 99%
“…Recently, the beneficial roles of bacteria in the coral holobiont have been investigated (6). These functions include defense against pathogens (12,13) and the cycling of nutrients such as nitrogen (14) and sulfur (15). Moreover, coral-associated bacteria have been proposed to be involved in coral resistance to bleaching (16,17), which has a devastating impact on reefs worldwide (4).…”
mentioning
confidence: 99%
“…typically have large genomes with highly versatile metabolic capabilities [ 54 ], and some have been shown to produce both algicidal and bactericidal compounds in culture. Indeed, cultures of coral-associated Ruegeria have been shown to inhibit growth of the coral pathogen Vibrio coralliilyticus [ 55 ]. While the vast majority of scar-associated ESVs are likely opportunists, these specific community members could be involved in limiting dysbiosis to the vicinity of the scar.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this genus is not only present in the core microbiome of healthy specimens O. patagonica, C. caespitosa and L. sarmentosa throughout the Mediterranean Sea, is also commonly associated with a large number of other coral species around the world (Huggett and Apprill, 2018; Rothing et al, 2020), even in larvae forms (Sharp et al, 2012; Zhou et al, 2017). It has been recently demonstrated that species belonging to this genus associated with corals show antibacterial activity against Vibrio coral pathogens (Miura et al, 2019) and provide essential vitamins like cobalamin (Karimi et al, 2019). Taken together, this OTU composed the core microbiome of geographically distant Anthozoans in the Mediterranean Sea and its abundance increased in necrotic tissues of their host under heat stress, highlighting the importance of this genus in marine invertebrate health during MHWs.…”
Section: Core Microbiome Of Anthozoans In the Mediterranean Seamentioning
confidence: 99%